Synthesis of hexacelsian barium aluminosilicate by film boiling chemical vapour process. Issue 9 (August 2020) - Besnard, C.; Allemand, A.; David, P.; Maillé, L.
Highlights: An original and rapid process to fabricate oxide/oxide composites is used : the film boiling chemical vapour. Three liquid precursors are used to elaborate the oxide matrix. A hexacelcian BAS is obtained at 1200 °C. Abstract: An original oxide/oxide ceramic-matrix composite containing mullite-based fibers and a barium aluminosilicate matrix has been synthesized by the film boiling chemical vapour infiltration process. Alkoxides were used as liquid precursors for aluminum, silicon and barium oxides. The structure and microstructure of the oxide matrix were characterized by Scanning Electron Microscopy, Energy Dispersive Spectroscopy and X-ray diffraction. Apart from small residual mullite and amorphous phase amounts, the oxide matrix is composed of the hexacelsian phase, conferring to the material interesting perspectives for high-temperature electromagnetic and structural applications.